2000
DOI: 10.1097/00005344-200002000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenosine Receptor Agonists on Efferent Renal Nerve Activity in Anesthetized Rats

Abstract: The aim of this study was to investigate the effects of A1 and A2 adenosine-receptor activation on the sympathetic nervous system. The effects on efferent renal nerve activity of selective A1 (CCPA; 2-chloro-N-6-cyclopentyladenosine) and A2 (2HE-NECA; 2-hexynyl-5'-N-ethylcarboxamidoadenosine) adenosine-receptor agonists were studied in anesthetized rats either with intact baroreflexes (intact rats) or with bilateral sinoaortic denervation and vagotomy (denervated rats). After a control period of 5 min, A1 or A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was demonstrated that adenosine modulated peripheral noradrenergic transmission [6]. Selective activation of A 1 and A 2 receptors elicits an increase in efferent renal nerve activity [7]. The question of whether adenosine interacts with autonomic nervous control of renal function remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that adenosine modulated peripheral noradrenergic transmission [6]. Selective activation of A 1 and A 2 receptors elicits an increase in efferent renal nerve activity [7]. The question of whether adenosine interacts with autonomic nervous control of renal function remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%